2011
DOI: 10.1007/s00424-011-0971-0
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar epithelial CNGA1 channels mediate cGMP-stimulated, amiloride-insensitive, lung liquid absorption

Abstract: Impairment of lung liquid absorption can lead to severe respiratory symptoms, such as those observed in pulmonary oedema. In the adult lung, liquid absorption is driven by cation transport through two pathways: a well-established amiloride-sensitive Na(+) channel (ENaC) and, more controversially, an amiloride-insensitive channel that may belong to the cyclic nucleotide-gated (CNG) channel family. Here, we show robust CNGA1 (but not CNGA2 or CNGA3) channel expression principally in rat alveolar type I cells; CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…It is well documented that amiloride specifically blocks LL absorption (2,23), as shown in our model when a Ϫ102% change (decrease) in LL absorption was observed after addition of amiloride (34). When PMA and ionomycin were given in conjunction with amiloride, no significant change in J v compared with that observed with administration of amiloride alone was seen.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…It is well documented that amiloride specifically blocks LL absorption (2,23), as shown in our model when a Ϫ102% change (decrease) in LL absorption was observed after addition of amiloride (34). When PMA and ionomycin were given in conjunction with amiloride, no significant change in J v compared with that observed with administration of amiloride alone was seen.…”
Section: Discussionsupporting
confidence: 67%
“…In our model, we have shown that terbutaline increased LL absorption by 157% (34). Administration of PMA and ionomycin to the lungs, together with ␤ 2 -mediated activation of ENaC, significantly reduced J v compared with administration of terbutaline (P ϭ 0.017; Fig.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Regulation of alveolar fluid homeostasis is based on active ion transport across the alveolar epithelium (1). Polarized localization and function of the basolateral Na-K-ATPase (Na pump) and apical sodium channels (2) are of crucial importance in transepithelial ion transport and the accompanying fluid clearance across the alveolar epithelial barrier (3,4).…”
mentioning
confidence: 99%